A práxis da tolerância como necessidade existencial nos processos educativos e na formação de educadores: contribuições de Paulo Freire - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The study object of this research is the tolerance praxis presented by Paulo Freire as an existential need in educational processes. The guiding question of the research is: What is the contribution of the assumptions of Paulo Freire's pedagogy regarding the tolerance praxis for teacher training and for educational processes in the constitution of critical, tolerant, solidary and democratic citizens? To answer this question, we defined as the general objective: Analyze the construction of the tolerance praxis in the theoretical assumptions of Paulo Freire and how this understanding presented by him can contribute to the construction and strengthening of more tolerant and respectful relationships in school contexts. We set out as specific objectives: a) analyze the propositions related to teacher training and work with tolerance found in scientific productions selected in digital libraries; b) discuss the importance of teacher training based on the tolerance praxis so that the educator is able to assist in the process of building more tolerant citizens from childhood. The epistemological basis of this research is found in Paulo Freire's theoretical assumptions. The bibliographical research, with a qualitative approach, focused at first on the procedures described mainly by Salvador (1978), as well as Lima and Mioto (2007), to later use Bardin’s content analysis (2004) for data processing and analysis. After examining Freire's productions, we observed a greater incidence of discussions about tolerance in works produced after the exile. Tolerance is presented by him as a revolutionary virtue, a requirement for democracy and an indispensable action for progressive teaching practices. Regarding the scientific works analyzed, despite using some of Freire's conceptions, such as banking education, none of them established relationships with the tolerance praxis and also did not seek to deepen the study of this concept in the light of Paulo Freire's thought. Regarding the search for proposition in scientific productions (articles, dissertations and theses) that contribute to an education based on the praxis of tolerance, we categorized them into: theoretical, practical and theoretical-practical. The articles presented only theoretical propositions. The dissertations and theses presented theoretical-practical contributions. None of the scientific work presented only practical propositions. Among the contributions indicated for the development of a tolerant education and for tolerance we highlight: the need for democratic management; didactics that stimulate creativity, autonomy and also value different identities; appreciation of the local culture; joint lesson planning; refuse any possibility of unquestionable, partial or neutral truths and that consequently recognize the possibility of fallibility; break with actions that reinforce competitiveness, individualism and the utilitarian character of education; promote the progressive discovery of the other, value differences, similarities and interdependence between subjects; encourage co-responsibility in conflict resolution; hold a mock trial with themes that address situations of crimes committed against black and indigenous people, homosexual relationships and low social class, in addition to investing in the training of teachers to prepare materials and carry out practices that allow students to develop new perceptions about social reality.
Keywords: Tolerância; Paulo Freire; Educação; Formação de professores/as; Tolerance; Paulo Freire; Education; Teacher training; CNPQ::CIENCIAS HUMANAS::EDUCACAO